Interpersonal, not existential, adversities predict postwar deterioration in youth social support - Kelly E. Dixon; Christopher M. Layne; Kimberly S. Ho Misiaszek; Chloe Golden (Academia Medicine)
Social support is a robust predictor of posttraumatic outcomes in diverse populations. Nevertheless, questions remain whether perceived social support is better conceptualized as the outgrowth of early attachment relationships that create capacities for interpersonal connection across development, or alternatively, as a more proximal, transactional, and dynamic interpersonal process that evolves under the influence of both prior and present life experiences. As applied to war-exposed youth, these unanswered questions impede efforts to build theory capable of identifying psychosocial mechanisms (early attachment relationships or ongoing interpersonal transactions?) and time frames (prewar, wartime, or postwar?) that influence the stability of perceived social support from youth’s support networks. This longitudinal study (N = 1,590 war-exposed Bosnian adolescents) used structural equation modeling to compare and contrast the predictive potency of three hypothesized contributors to adolescents’ postwar perceived social support: (a) prewar disruptions in early attachment relationships, (b) wartime and postwar interpersonal adversities, and (c) wartime and postwar adverse living conditions. Adolescents completed the War Trauma and Adversities Inventory at Time 1 and the Multi-Sector Social Support Inventory (assessing perceived social support from youths’ nuclear family, extended family, adult friends and mentors, and same-age peer social network sectors) six months later at Time 2. Prewar disruptions in attachment relationships predicted deteriorations in perceived social support across all network sectors, and wartime/postwar interpersonal adversities exerted differential (sector-specific) predictive effects on perceived social support. In contrast, adverse living conditions did not exert predictive effects on any sectors of adolescent perceived social support.